2023
DOI: 10.3389/fpsyg.2023.1116321
|View full text |Cite
|
Sign up to set email alerts
|

Motivation to teach and preparedness for teaching among preservice teachers in China: The effect of conscientiousness and constructivist teaching beliefs

Abstract: “Preparedness for teaching” refers to the degree of confidence preservice teachers have, and reflects their ability. Developing preparedness for teaching is an important part of preservice teachers’ professionalization. A substantial body of literature has documented the critical influence of the motivation to teach on preparedness; however, how this relation is impacted by mediating and moderating mechanisms remains unclear. To respond to this gap in knowledge, the present study constructed a mediated moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 114 publications
1
0
0
Order By: Relevance
“…Notably, we found that the participants' internal MT had a higher mean value than their external MT. This suggests that the Chinese teachers' motivation to teach is predominantly internal-a finding that is consistent with several previous China-based studies [53,54]. Teachers' motivational characteristics may be closely related to the social and cultural background of China, as China possesses a cultural tradition that honors teachers, practices collectivist values, and holds the dedication of teachers in higher esteem.…”
Section: Mediating Role Of Teachers' Motivation To Teach and Self-eff...supporting
confidence: 86%
“…Notably, we found that the participants' internal MT had a higher mean value than their external MT. This suggests that the Chinese teachers' motivation to teach is predominantly internal-a finding that is consistent with several previous China-based studies [53,54]. Teachers' motivational characteristics may be closely related to the social and cultural background of China, as China possesses a cultural tradition that honors teachers, practices collectivist values, and holds the dedication of teachers in higher esteem.…”
Section: Mediating Role Of Teachers' Motivation To Teach and Self-eff...supporting
confidence: 86%